Rasgos psicopáticos y su asociación con depresión, ansiedad y factores sociodemográficos en estudiantes de medicina peruanos - Fernández-Apolaya, Jesús (2023)
Introduction: Psychopathic traits harm the professional development and interpersonal relations of the general population, including healthcare professionals. This can be seen not only in already licensed physicians, but it may also be evidenced since their formative years as medical students. Objective: To evaluate the presence of psychopathic traits in a sample of Peruvian medical students and determining whether there is an association between sociodemographic and mental health (depression and anxiety) characteristics on the levels of psychopathic traits. Methods: A cross-sectional study was conducted on 497 students of a Peruvian medical school. Through online questionnaires, the following instruments were self-administered: Levenson Self-Report Psychopathy Scale (LSRP), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7). Results: 19.7% of the participants were in the psychopathic group. The variables associated with a higher frequency of belonging to the psychopathic group were male sex (aPR = 2.10, 95% CI: 1.58-2.79, p < 0.05), having clinically relevant depressive (aPR = 2.05, 95% CI: 1.41-2.96, p < 0.05) and anxious symptoms (aPR = 1.46, 95% CI: 1.01-2.09, p < 0.05). Conclusions: Medical students of the sample studied show a high prevalence of psychopathy traits. The variables associated with a higher frequency of belonging to the psychopathic group were male sex, having clinically relevant depressive symptoms, and anxiety symptoms. More involvement on behalf of the medical school is necessary as to the identification of the psychopathic traits in medical students.